Language Attitude of State High School Students 3 Waeapo, Buru Regency Towards The Use of Indonesian Language in The Millenial Era - Indrayani, Nanik; Muspiha, Muspiha; Susiati, Susiati (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
SMA Negeri 3 is a favorite school in Waeapo District, Buru Regency, Maluku. There are several ethnic groups in the school environment at SMA Negeri 3, including the indigenous tribes, namely the Buru tribe and immigrant tribes such as Ambon, Southeast Maluku (especially Kei), Ambalau, Islands Sula (especially Sanana), Butonese, Bugis, Makassarese, Javanese, Sundanese. He also uses various languages, including Ambonese Malay dialect, Butonese, Bugis, Makassarese, Javanese, and also Sundanese. The general objectives of this study are: 1) to identify the influence of language attitudes of students at SMA Negeri 3 Waeapo, Buru district on the use of Indonesian in the Millennial Era; 2) revealing the positive and negative effects of the Language Attitudes of Students of SMA Negeri 3 Waeapo, Buru Regency on the Use of Indonesian in the Millennial Era. The type of research used in this research is a descriptive qualitative field research which examines linguistic phenomena. The data and data sources in this study are primary data and secondary data. The location of this research is SMA Negeri 3 Waeapo. The method of data collection was done through non-participating observation. The data collection technique was carried out through the free-of-conversation listening technique, recording technique, and note-taking technique. The data that has been classified is then analyzed using qualitative descriptive analysis techniques. The results of the study are positive factors and there are negative factors from the use of the Ambonese Malay dialect. The positive factor is that students continue to use Ambonese Malay dialect which is a language loyalty and encourages people of a language to maintain their language, this is a language pride that encourages people to develop language and use it as a symbol of identity and community unity, as well as awareness of the existence of language norms that encourage people to use their language carefully and politely, so that students from the Javanese and Sundanese tribes are finally interested in using Ambonese Malay dialect. The negative factor is that the students who come from the Javanese tribe feel offended because they don't know the meaning of the Ambonese Malay dialect which is known to be rough according to the Javanese people who are known to be smooth in speech.